Pemberdayaan Pokdarwis di Desa Sumberklampok Gerokgak Buleleng Melalui Edukasi Literasi Keuangan, Branding Wisata dan Pengembangan Sumber Daya Manusia Kreatif Berbasis Ekonomi Hindu - Duwi Oktaviana; Komang Dewi Susanti; Ni Ketut Raka Utariani; Nyoman Widyani; Nyoman Dane (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Tourism Awareness Groups (Pokdarwis) play a crucial role in community-based tourism development; however, they continue to face various challenges, particularly in financial literacy, tourism branding, and creative human resource development. This community service program aimed to enhance the capacity of Pokdarwis in Sumberkelampok Village, Gerokgak District, Buleleng Regency through financial literacy education, tourism branding enhancement, and creative human resource development based on Hindu economic principles. The program employed the Participatory Rural Appraisal (PRA) approach combined with educational activities, training, mentoring, and participatory evaluation. The implementation process included needs assessment, financial literacy training, tourism branding workshops, creative economy development, internalization of Hindu economic values, and program implementation assistance. The results indicated significant improvements in participants’ ability to prepare simple bookkeeping records, develop promotional strategies and digital marketing media for tourism destinations, and identify superior creative economic products based on local potential. Furthermore, participants demonstrated a greater understanding of the concepts of Tri Hita Karana, Tat Twam Asi, and Arthasastra as fundamental principles for sustainable tourism management. All program success indicators were achieved, including participant attendance, improved financial literacy, preparation of simple bookkeeping documents, development of tourism promotional media, identification of creative economy products, formulation of follow-up action plans, and active participation of Pokdarwis members. The program successfully strengthened both the individual and institutional capacities of Pokdarwis in managing professional, competitive, and sustainable tourism destinations grounded in Hindu economic values.